Driving Economic Growth in Home Industries Through the Art of Mangrove Batik - Adilla Kustya Ulfa; Tito Aditya Perdana; Febrianur Ibnu Fitroh Sukono Putra; Risanda Alirastra Budiantoro (JOCESS : The Journal of Community Empowerment and Sustainability Services, 2025)
Batik has long been known as a work of the Indonesian people. Judging from the source of the textile dyes obtained, it is divided into two, namely synthetic dyes and natural dyes. From now on, referred to as Bakau, Mangrove Batik is a batik that uses natural dyes because the mangrove parts used as dyes are waste or unused plant parts. The main problem faced by Batik Bakau, our target partner in the home industry, is the need for more awareness of the products produced by the producers to their consumers. The next problem is the less-than-optimal use of the existing marketplace platform to market products that the Batik Bakau home industry has made. Creating a good and attractive social media design for consumers is also necessary to empower this home business. The methods used are counseling and socialization of community partnership programs, Training in the formation of a mindset for the potential use of digital marketing, Strengthening digital platforms to facilitate mangrove batik business actors in marketing their products, Branding and packaging training to improve the quality of human resources for mangrove batik home industry business actors, Digital marketing training through the digital platform that has been provided to increase awareness, interest, and sales of mangrove batik. The results obtained are in the process of improving entrepreneurial skills through the use of e-commerce as a business startup media carried out in stages: (1) IbM method, namely training in registration and management of e-commerce profiles; (2) Managing e-commerce accounts periodically until sales occur; (3) Selling and making reports on online businesses that have been run.